Strategi Koping Pelampiasan Stres pada Mahasiswa Rantau - Vira Fatihatun Najah (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2024)
Individuals who decide to migrate to continue their education and improve their quality of life will undoubtedly face various new problems with themselves and their surroundings. The many issues faced by students who are away from home can cause them to experience stress. In dealing with this stress, each student away from home has a different way. This paper aims to determine coping strategies for stress relief from the perspective of the phenomenology of students who are away from home. The research method used is qualitative descriptive, which is collected data through interviews with two informants from different campuses. The results of the study show that the reasons why students who are away from home experience stress are due to pressure in the world of lectures and also other problems that they face simultaneously. The coping strategies used are in two forms: coping strategies that focus on emotions and those that focus on meaning. Keywords: Students Who Are Away, Stress, Coping Strategies